DEIXIS IN JOHN LEGEND’S SONGS - Desmalia Purba (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2018)
This study discusses about Deixis. It is the term from Greek which means pointing by language. This study aims at finding the types of Deixis used in John Legend’s selected songs’ lyrics and finding the types of Deixis most dominantly used in John Legend’s selected songs’ lyrics. This study was applied by using descriptive qualitative design. Having analyzed the data, the findings of this study are: (a)There are three kinds of deixis found in John Legend’s songs, they are person deixis, time deixis and place deixis; (b) Person deixis is the most dominantly used in John Legend’s songs; 86.86%. The writer suggests that the students should learn Deixis as clear as possible because it is the most fundamental thing that should be mastered and the teacher or instructor of English language can teach the students about Deixis by using many written forms, such as songs’ lyrics, poems, novels, drama’s scripts and others.